The impacts of antipsychotic medications on eating-related outcomes: A mixed methods systematic review. - Rasha Alkholy; Karina Lovell; Penny Bee; Rebecca Pedley; Helen Louise Brooks; Richard J Drake; Prathiba Chitsabesan; Anam Bhutta; Abigail Brown; Rebecca L Jenkins; Andrew Grundy (PLoS ONE)
Background Almost all antipsychotics are associated with weight gain. Given the gravity of this side-effect and its consequences, it is imperative to understand the mechanisms involved. One mechanism that could contribute to this side effect is the impact of antipsychotics on eating-related outcomes. Objective We aimed to synthesise the available quantitative research on the effects of first- and second-generation antipsychotics on eating-related outcomes, and qualitative research exploring people's experiences with these medications in relation to appetite and eating behaviours (PROSPERO protocol CRD42022340211). Methods We searched Medline, PsycInfo, and Web of Science from inception to 9 May 2024. Quantitative data were synthesised without meta-analysis using vote counting based on direction of effect. Qualitative data were synthesised using thematic synthesis. Results Searches identified 8,746 citations yielding 61 separate studies; 55 quantitative and 6 qualitative, published 1982-2024. Using GRADE, our assessment of the quantitative review findings ranged from low to very low-level certainty. Given the lack of direct evidence from high-quality placebo-controlled trials, it is pertinent to interpret the quantitative findings with caution. Using GRADE-CERQual, our assessment of the qualitative review findings ranged from low to very low-level certainty; these findings suggest that the relationship between antipsychotics and food intake is influenced by an interplay of individual, interpersonal and external factors, the most significant of which is food environment. Limitations The internal validity of this review was affected by the serious limitations of the included quantitative studies and the paucity of qualitative evidence. Strengths We used GRADE and GRADE-CERQual frameworks to enhance the transparency of our judgement of the certainty of the evidence. Lived experience perspectives were incorporated in different stages of the review to enhance its relevance and practical implications. Conclusions There is insufficient evidence from well-conducted studies to determine the effect of antipsychotics on eating-related outcomes.